VISUAL-SPATIAL INTELLIGENCE PROFILES OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING GEOMETRY PROBLEMS - Annisa Azkia; Nailul Authary; Nazariah Nazariah (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2025)
This study is entitled The Profile of Junior High School Students’ Visual-Spatial Intelligence in Solving Geometry Problems. The purpose of this research is to describe the visual-spatial intelligence profile of junior high school students in solving geometry problems. This study employed a qualitative approach using a descriptive research design. The research subjects were selected based on visual-spatial intelligence levels, which were categorized into high, moderate, and low. Data were collected through geometry problem-solving tests, in-depth interviews, and documentation of students’ work. The data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that students with high visual-spatial intelligence are able to visualize geometric shapes clearly, organize problem-solving steps systematically, and apply concepts and formulas accurately. Students with moderate visual-spatial intelligence show sufficient understanding of geometry problems but experience limitations in visualization and accuracy. Meanwhile, students with low visual-spatial intelligence encounter difficulties in visualizing geometric forms, understanding concepts, and tend to rely on memorizing formulas without conceptual comprehension. These findings demonstrate that visual-spatial intelligence plays a crucial role in students’ success in solving geometry problems, highlighting the importance of instructional strategies that emphasize visualization and the use of appropriate learning media